Business Performance In Entrepreneurship Study In The Process Of Student Business Sustainability - Wahyu Utami, Indah; Osman, Sharina; Nur Savira Dewi Saputri, Lisa; Diva Febriana, Valentina (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Business sustainability is a concept that makes business beneficial for the economy and the environment and people's lives. One of the indicators of business sustainability is the optimization of business performance. Student business startups are businesses run by students that are expected to produce sustainable business performance. Business performance in entrepreneurship studies in clouding the business sustainability process of students needs to be carried out through the implementation of Green HRM (GHRM) by focusing on human resource practices and entrepreneurial intentions owned by students. If you have optimized good business performance, so that in the future it can increase business sustainability among entrepreneurial students.